Relation between Behavioral Factors, Malnutrition and Persistent Diarrhea in Children Under Two Years of Age. A Hospital Study - Al-Badri, Adel A.; Al Ammary, Makaei A.F.; Al-Badawi, Ghazwan G.; Al Azawi, Shehab A. (Journal of the Faculty of Medicine Baghdad, 2007)
Background A high prevalence of Behaviors which is related to persistent diarrhea and the prevalence of moderate to sever malnutrition in patients with persistent diarrhea in children.Objectives To asses the prevalence of negative behaviors that causes the persistent diarrhea and to asses the prevalence of malnutrition among children with persistent diarrhea and tocompare prevalence of malnutrition due to persistent diarrhea to that of national figures.Patients and Methods This study was carried out at the Central Teaching Hospital for Children in Baghdad, a total number of 200 cases of persistent diarrhea (lasting more than 14days)"with no more than 48 hour normal bowel motions in this period" in children less than 2 years of age. The period of the study was one year from the 1st of January 1999 to the thirty-one of December 1999. Information was taken from patient's companions usually the mothers and the patients were selected at Inpatient, out patient and Emergency departments in a randomized way.Results. The study showed that the most common age group of persistent diarrhea was the 2nd half of the first year constituting (47%) (94/200) of patients with persistent diarrhea. Patients whose mothers were illiterate constituted a high proportion (48%) (96/200). Patients on bottle or mixed feeding constituted (77%) (144/200). A high prevalence of some behaviors which is related to persistent diarrhea was noticed like allowing the children to pick up food spilled on the floor and eat it (65%) (130/200), stopping or altering feeding during episodes of diarrhea (78%) (156/200), mothers neglecting washing hands or their babies hands before feeding their children (74%) (148/200) and (66%) (132/200) respectively, failure to introduce solid food in 1st year of life (72.3%) (94/ 130) and failure to eat adult type of food in 2nd year of life (65.7%) (46/ 70). The prevalence of moderate to sever malnutrition at the three age groups was significantly higher in children with persistent diarrhea in present study compared to general population figures reported by polio immunization national day (PIND) survey at 1999 in Iraq, marasmus was significantly more common in 2nd half of the 1st year of life and the prevalence of kwashiorkor was significantly higher (15.8%) (11/70) among the older age group (2nd year of life)Conclusion. The most common age group who developed persistent diarrhea was the second half of the first year of life. The negative behaviors of the mothers had a significant effect on the occurrence of persistent diarrhea in children and the development of malnutrition diseases like marsmus and kwashiorkor